A SIMPLIFIED ELECTRICAL NETWORK MODEL FOR TECHNO-ECONOMIC ANALYSIS OF GLOBALLY INTEGRATED ELECTRICITY MARKET - Giulia Crespi; Zhengyi Han; Tao Huang; Ettore Bompard; S. Corgnati (Itecons - Instituto de Investigação e Desenvolvimento Tecnológico para a Construção, Energia, Ambiente e Sustentabilidade, 2019)
The decarbonization of current power system is a crucial issue that policy makers are facing worldwide. Higher integration of renewable energy and greater enduses electrification are the basis of the Global Energy Interconnection (GEI) vision, which is based on the deployment of renewable sources in energy-rich remote areas (i.e. Africa and Arctic region, rich of solar and wind power, respectively) and on the use of Ultra High Voltage (UHV) power lines, mainly direct current (DC), to redistribute this clean energy to the major load. The paper presents a first attempt of modelling and simulating an electricity interconnected system, through optimal power flow simulation. By modelling generations and installed capacities by fuels and loads per the selected 15 world regions, generation and consumption were simulated for a typical winter day, with the assumptions of global electricity market and null transmission constraints. Moreover, to assess the interconnection between the different areas in economic terms, a new metric was defined, named “net electricity trading indicator”, which aims at evaluating the remaining wealth in the geographical zones, in case of presence of an interconnected power system.